2019
DOI: 10.1002/bit.27004
|View full text |Cite
|
Sign up to set email alerts
|

Parallel experimental evolution reveals a novel repressive control of GalP on xylose fermentation in Escherichia coli

Abstract: Efficient xylose utilization will facilitate microbial conversion of lignocellulosic sugar mixtures into valuable products. In Escherichia coli, xylose catabolism is controlled by carbon catabolite repression (CCR). However, in E. coli such as the succinateproducing strain KJ122 with disrupted CCR, xylose utilization is still inhibited under fermentative conditions. To probe the underlying genetic mechanisms inhibiting xylose utilization, we evolved KJ122 to enhance its xylose fermentation abilities in paralle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…This result indicates that Glf is able to serve as an efficient transporter for both glucose and xylose. Our previous work suggests that utilization of GalP as a substitute glucose transporter is undesirable for conversion of lignocellulosic sugar mixtures because GalP represses xylose fermentation and uses proton gradients (Kurgan, Sievert, et al, 2019 ). Thus, Glf is a more suitable substitute glucose transporter for lignocellulosic bioconversion compared to GalP since Glf is more energy efficient and has no repressive effect on xylose fermentation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This result indicates that Glf is able to serve as an efficient transporter for both glucose and xylose. Our previous work suggests that utilization of GalP as a substitute glucose transporter is undesirable for conversion of lignocellulosic sugar mixtures because GalP represses xylose fermentation and uses proton gradients (Kurgan, Sievert, et al, 2019 ). Thus, Glf is a more suitable substitute glucose transporter for lignocellulosic bioconversion compared to GalP since Glf is more energy efficient and has no repressive effect on xylose fermentation.…”
Section: Resultsmentioning
confidence: 99%
“…When performing cosugar fermentations, 66 g l –1 glucose and 34 g l –1 xylose were used, a typical mass ratio representative of lignocellulosic sugar compositions (Saha, 2003 ). 100 mg l –1 ampicillin and 10 µM IPTG were included in all fermentation tests for the cells with plasmids to maintain the plasmids and induce suitable expression for transporter genes as previously described (Kurgan, et al, 2019a , b ). All batch fermentations were inoculated using an initial OD 550nm of 0.05 and fermentation was controlled at 37°C and pH 7.0 with automatic additions of 6 M potassium hydroxide.…”
Section: Methodsmentioning
confidence: 99%
“…Remarkably, resulting PTS − mutants abolishing the CCR or inducer exclusion mechanisms can simultaneously use glucose and xylose mixtures as carbon sources for production metabolite purposes such as succinate and cis, cis-muconic acid, demonstrating that product yield and productivity were significantly improved in these PTS − mutants ( Table 3 ). The overexpression of GalP in the Δ galP derivative strain of E. coli KJ122 showed a negative regulatory control mechanism of the expression of catabolic genes of other sugars such as xylose and arabinose, suggesting that the selection of GalP as the leading glucose transporter in the PTS − derivative was an efficient strategy [ 28 , 82 ].…”
Section: Transport Engineering or Improving Sugar Uptake Capabilities...mentioning
confidence: 99%
“…It has been found that some intermediates produced from glucose can inhibit the transcription of genes for other sugars' metabolism ( Lu et al, 2016 ; Vinuselvi et al, 2012 ). CCR is a global regulatory mechanism of bacteria, and about 5–10% of genes in bacteria are regulated by CCR ( Kurgan et al, 2019 ).…”
Section: Microbial Metabolic Engineering For Enhanced Utilization Of ...mentioning
confidence: 99%